An experimental investigation of mental accounting in environmental economics. (2016) - Gruener, Sven; Hirschauer, Norbert
Using a business management game design for the primary sector, the authors experimentally investigate whether and how mental accounting affects decision making in an institutional context of environmental taxes. The subject of this investigation is scientifically and socially relevant because taxes are both widely discussed in environmental economics and used as a regulatory tool in environmental politics. This study shows that by attaching the label 'environmental' on a general tax that is payable regardless of decisions made decreases agents' inclinations to use environmentally-friendly practices. The authors interpret this observation as an indication for mental accounting. In other words, the authors found empirical evidence that people are less prepared to forego profits and adopt environmentally-friendly practices if they feel that they have already made a contribution in the category 'environment'. Mental accounting represents an important case of context-dependent decision making that needs to be considered both in the explanation and the conditional forecasting of behaviour.